The Political Party Intervention Has A Negative Impact On Dpr Policy : Case Study Of The Revision Of The Tni Bill - iksan (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to examine the impact of political party intervention on the legislative process in the house of representatives (DPR) with a focus on a case study of the revision of the Indonesian national army law (RUU TNI). The urgency of this writing is the increasing public concern about the degradation of legislative independence which should represent the interests of the people, not partisan interests. This study was conducted using a normative legal method approach with a critical study of the dynamics of DPR policy politics, which has an effect on the integrity of legislation and public trust. The novelty of this study is in the intervention of political parties on the revision process of the TNI Bill, which obscures the professional principles of active TNI members in the democratic system and civil supremacy which has the potential to weaken the checks and balance mechanism in the system. The results of this study indicate that political party intervention is very clear in the interests of power that are certain groups that eliminate the substance of law and public involvement in the revision of the TNI Bill.